Effect of oestriol gel on dyspareunia in postmenopausal women in 2 weeks of treatment: a pilot study. (3rd October 2022) - Cuerva, Marcos J.; González, Silvia P.; Lazaro-Carrasco De La Fuente, Jesús; Lopez, Francisco J.; Nieto, Concepción
Abstract: This brief report evaluates the early effect of ultra-low dose 0.005% oestriol vaginal gel on dyspareunia in postmenopausal women within the first 2 weeks of treatment. This was a prospective and multicentre single-arm pilot study and the effect of the treatment on dyspareunia was evaluated by using a diary. In total 23 women and 150 coitus were studied. 8 coitus were painless in the first week and 42 during the second week ( p < .0001). A reduction in pain from the baseline was seen in 116 (77.3%) out of the 150 coitus. 0.005% oestriol vaginal gel produced a rapid and progressive improvement in dyspareunia from the very first days of treatment in postmenopausal women. IMPACT STATEMENT: What is already known on this subject? Local oestrogen therapy has shown efficacy in the treatment of genitourinary syndrome of menopause (GSM) and dyspareunia when used for a duration of greater than 3 weeks. What do the results of this study add? This study shows that the use of oestriol gel produces clinical effects from the beginning of its use, decreasing dyspareunia in postmenopausal women within just 14 days of daily use. What are the implications of these findings for clinical practice and/or further research? In cases of dyspareunia in relation to menopause, therapy with local oestrogens, in our case oestriol gel, produces an improvement from the beginning of its use. This information is clinically relevant when evaluating therapeutic options.